176k views
1 vote
Question 1: Solve the system. Use the substitution method.
.A
.B
.C
.D

Question 1: Solve the system. Use the substitution method. .A .B .C .D-example-1

1 Answer

3 votes

Answer:

C) No solution

Explanation:

Because we know that y=3x-2, we can substitute the value of y into the first equation to get x:

-6x+2y=-6

-6x+2(3x-2)=-6

-6x+6x-4=-6

-4=-6

However, there is one problem! Since both sides are not equal to each other, there's no solution. Therefore, C is the only correct answer.

User Infinito
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.